Molar Pregnancy in Cesarean Section Scar: A Case Report and Literature Review - Daggez, Mine; Dolanbay, Mehmet (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Molar pregnancy in cesarean scar is an extremely rare condition. It has a high risk of uterine rupture and bleeding. There is a small number of case reports in the literature, so the optimal diagnostic algorithms and management are not clear. We reported a 25-year-old woman who presented to our clinic with amenorrhea for 40 days and vaginal bleeding for 3 days. Transvaginal ultrasonography and serum human chorionic gonadotropin (hCG) level raised suspicion of a molar cesarean scar pregnancy (CSP). Magnetic resonance imaging (MRI) was conducted for further knowledge of the characteristics of the mass. Careful suction curettage under ultrasound guidance was performed. The histologic examination of the tissue confirmed a partial hydatidiform mole. The differential diagnosis between CSP and molar CSP is extremely challenging. Serum hCG, sonogram, and MRI are our tools, but none of them suffice for a definitive diagnosis. Histological examination of the postoperative sample is still the gold standard for the diagnosis of molar CSP; however, MRI can assist in planning the necessary interventions.
Keywords: Doppler ultrasound; pregnancy; cesarean scar pregnancy; magnetic resonance imaging; molar pregnancy; cesarean section